The Sustainable Rural Development Strategies of The North-East Region of Romania - Mintenica BUTNARU (CIUSTEA); Stejarel BREZULEANU (Communications of International Proceedings, 2022)
In recent decades, Romania has faced enormous challenges in reaching its economic and social potential, in the agri-food and forestry sector, as well as in rural areas. Gross domestic product per capita was and is much lower than the European Union average and significantly lower in all rural areas, showing a very slow process of economic growth. From the point of view of development, rural areas have a significant gap compared to urban areas and are characterized by: persistent structural deficiencies (large number of people employed in agriculture, aging population, a large number of subsistence farms, etc.); low added value of agri-food products; low labor yields and productivity; weak entrepreneurial spirit for the development of economic activities, reduced access to credit; a dysfunctional land market; a modest export orientation; insufficient investment in research and development; the continuous increase of regional disparities; a high share of the population exposed to the risk of poverty and social exclusion, etc. In this context, the paper aimed to identify how to approach sustainable development in regional development strategies, with the Northeast Region as a case study, and to assess how to implement strategic objectives, regionally and in rural areas. The paper aims to identify new strategic proposals to ensure the sustainable development of rural areas, by using a system of specific, quantifiable and representative indicators that allow, through econometric analysis, evaluation of results and projection of the evolution of sustainable development.
Keywords: sustainable development; development strategy; strategic objectives